Management Strategies of Laringopharyngeal Reflux - Fitria, Hidayatul (Jurnal KESANS : Kesehatan dan Sains, 2025)
Laringofaringeal reflux is the retrograde movement of gastric contents that cause symptoms in the larynx. Laringopharingeal reflux symptoms include dysphonia, globus faringeus, mild dysphagia, chronic cough and throat clearing. Physical examination found edema posterior comisura, edema vocal cord, ventricular obliteration and pseudosulcus. Diagnosis can be established by Reflux Symptom Index (RSI), Reflux Finding Score (RFI), dual pH probe monitoring and the use of  PPI empiric. Management of   laryngopharingeal reflux are  intervention of dietary,  lifestyle modification and  proton pump inhibitor (PPI) medication. Reported a case of 48-year-old female patient who was diagnosed with laringopharingeal reflux and gave medicamentosa followed a diet and lifestyle modification. There are  improvement of RSI and RFI after therapy.